Combining online journalism and self-digitization: a new practical approach - Tiago Gama Rocha (2015)
The Golden Triangle of Technology, social, mobile and real-time, accelerated the establishment of the always-on society. In the field of journalism in particular, the collision between digital technologies and journalism is tale of disruption. With the advent of automatic curated platforms, a new discussion emerges: human versus algorithm editing. While human-editing does not allow for personalized distribution, algorithms do. In this scenario, as opposed to a wider and more universal social experience, our audience individual footprint becomes of the utmost importance. Wearable Technology (WT) has the potential to add another layer to our individual footprint since it extends and augments the communication bandwidth between human and machine. This can be achieved by tracing our physiological reactions. At a more practical level, for journalism in particular, it can affect the quality of personalized news distribution. In this research, we developed a system that enables the penetration of WT in journalism. Our objective is to understand whether the used physiological metrics are valid inputs for a real-time system designed to maximize the quality of user experience. We present the methodological design and discuss how WT can be used algorithmediting and personalized-distribution. Authors already pleads for the field of journalism to turn their attention towards WT. They address how WT can work both as a new distribution medium and as a tool for creating content. However, she neglects the disruptive nature of combining journalism and self-digitalization. Furthermore, there is still a lack of research linking WT and distribution. We first built an interface to receive and process physiological data from biosensors that measure data from electrodermal-system and cardiovascular system. Then, a synchronistic platform was created to record metadata from visited news and physiological metrics from the user. When the efficiency of this technology was tested, the experimental study took place. In our experimental study, the first task consists of subjects navigating a tablet news aggregator while using the biosensors. In the second task, users accessed a personalized curation of the news. Such personalization was based on the individual levels of arousal extracted from the first task. We analyzed the results focusing on the quality of user experience in the second experiment, both per si and by comparison with the first. We conclude by addressing the gaps to be fulfilled in order fully operationalize such a system, as well as the ethical implications of augmenting the communication bandwidth between audiences and journalism. Our work provides a systematic overview of the growing use of WT in society, as well as practical insights into the use of these devices as add-ons to the quality of news distribution and user experience. Whatever the next incarnation of journalism should look like, people will be at the center of it.